A Specific Time Lag Regulation of Soil Moisture Across Layers on Soil Salinization in the Northeast Tibetan Plateau Agroecosystem - Di Wei; Ziqi Zhang; Lin Yan; Jia Yu; Yun Zhang; Bo Wang (Agriculture)
The evaporation of soil water drives the upward movement of salt and its accumulation on the surface, which ultimately leads to soil salinization in agroecosystems. With the rapid development of remote sensing technology, the soil water and salt transport can be monitored accurately. Based on Landsat 8 satellite imagery and ERA5-Land reanalysis datasets, this study explored the variation characteristics of soil water and salt in the northeast Tibetan Plateau from 2013 to 2023, inferred by geostatistical methods like ridge regression, windowed cross correlation, and machine learning algorithms. The results show that the negative correlation effect between deep soil moisture (100–289 cm) and soil salinization is stronger. Moreover, soil water and salt also have a time lag effect compared with instant responses, meaning that the soil salinization caused by deep soil moisture may require longer transport times. As the potential driving factors, an increase in soil organic carbon and runoff is beneficial for alleviating salinization while abundant runoff also promotes soil humidification. This study has elucidated the specific regulation of soil salinization by soil moisture within different profiles, which is beneficial for understanding the ecological balance of soil water and soil salt in agroecosystems.